2012
DOI: 10.1002/chem.201201291
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray Absorption Spectroscopic, Crystallographic, Theoretical (DFT) and Chemical Evidence for a Chalcogen–Chalcogen Two‐Center/Three‐Electron Half Bond in an Unprecedented “Subselenide” Se23− Ligand

Abstract: Doing things by halves: The dimeric compound (Cp'Ni)(2)(μ(2)-Se(2)) (Cp' = 1,2,3,4-tetraisopropylcyclopentadienyl), shown in the scheme, was investigated by using low temperature X-ray crystallography and X-ray absorption spectroscopy. The Se K-edge energy strongly indicates a Se physical oxidation state of -1.5, consistent with an unprecedented two-center/three-electron half-bonded Se(2)(3-) or "subselenide" ion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Complex 5 was isolated in 31% yield and 90% purity; some unidentified minor byproducts could not be completely separated from 5 by washing or crystallization. In comparison, the reaction with elemental selenium afforded the dinuclear complex [(Cp Ar Ni) 2 (μ-Se 2 )] ( 6 , Scheme ), which is a rare molecular subselenide, with the only other example being [{( i Pr 4 C 5 H)­Ni} 2 (μ-Se) 2 ]. , It is important to mention that dinuclear chalcogenides such as in situ generated [(C 5 Me 5 )­M­(μ-S)] 2 (M = Ru, Rh, Ir) dimerize to cubane-type clusters [(C 5 Me 5 )­M­(μ 3 -S)] 4 , presumably due to the lower steric effect of the pentamethyl cyclopentadienyl ligand. , …”
Section: Resultsmentioning
confidence: 99%
“…Complex 5 was isolated in 31% yield and 90% purity; some unidentified minor byproducts could not be completely separated from 5 by washing or crystallization. In comparison, the reaction with elemental selenium afforded the dinuclear complex [(Cp Ar Ni) 2 (μ-Se 2 )] ( 6 , Scheme ), which is a rare molecular subselenide, with the only other example being [{( i Pr 4 C 5 H)­Ni} 2 (μ-Se) 2 ]. , It is important to mention that dinuclear chalcogenides such as in situ generated [(C 5 Me 5 )­M­(μ-S)] 2 (M = Ru, Rh, Ir) dimerize to cubane-type clusters [(C 5 Me 5 )­M­(μ 3 -S)] 4 , presumably due to the lower steric effect of the pentamethyl cyclopentadienyl ligand. , …”
Section: Resultsmentioning
confidence: 99%
“…These follow the expected trend, with a decrease in the edge energy as the Se oxidation number decreases. The Sitzmann Cp′ 2 Ni 2 Se 2 compound has an edge energy lower than all of the compounds in our test set, which, via extrapolation of the linear trend in Se oxidation states, corresponds to an oxidation state of −1.5 for the Se atoms in the compound, indicative of an Se 2 3– ligand …”
Section: C/3e Bonds In Main Group Chemistrymentioning
confidence: 90%
“…Inset: Correlation of the Se edge energies with Se oxidation states, including the data point for Cp′ 2 Ni 2 Se 2 suggesting a Se oxidation state of −1.5. Figure adapted from ref . Copyright 2012 John Wiley and Sons.…”
Section: C/3e Bonds In Main Group Chemistrymentioning
confidence: 99%
“…14 Use of a microporous (o0.5 nm pore size) carbon matrix alleviates the characteristic capacity loss of Li 2 S batteries; the effect was attributed to restricted growth of sulfur molecules within the pores which in turn limits formation of soluble Li 2 S n (n = 4-8). 15 The first MAS-NMR study of polycrystalline Bi 2 E 3 (E = Se, Te) measured very different T 1 for 125 Te (76 ms) and 77 Se (0.63 s), and revealed that coupling to the conduction band electrons at the chalcogenide sites is much stronger in the telluride due to spin-orbit coupling. 16 A ZT value ca.…”
Section: Oxidesmentioning
confidence: 99%
“…) ion. 77 [(N(SiMe 3 ) 2 ) 3 U] 2 (m-E) (E = S, Se Te) were obtained from U(N(SiMe 3 ) 2 ) 3 and the elemental chalcogen; in the case of sulfur, presence of U(CH 2 SiMe 2 NSiMe 3 ) (N(SiMe 3 ) 2 ) 2 , induces the formation of [(N(SiMe 3 ) 2 ) 3 U] 2 (m-Z 2 :Z 2 -S 2 ). 78 The anion within the structure of Na 4 [(UO 2 )(S 2 ) 3 ] (CH 3 OH) 8 displays coordination of UO 2 2+ by bidentate S 2 2À anions; computational modeling (CASSCF/CASPT2) indicates that the U-(S 2 )-U unit would be bent and suggests that such motif would be useful in the construction of large cage clusters.…”
Section: àmentioning
confidence: 99%